DIALEKTIKA PEMIKIRAN ISLAM DAN DEMOKRASI MANHAJ INDONESIA: SEBUAH POTRET HISTORISITAS , KONTINUITAS, DAN PERUBAHAN - Moh. Anas Kholish; Yulianto Yulianto (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2019)
Various responses arise when Islam and democracy met. Disagreement and dissent is something that cannot be prevented. The complexity of the problem is increasing when democracy is held in the context of Indonesian politics. Indonesia has its own cultural roots which may be in some ways incompatible with democracy born from western culture and promoted through colonialism. Thus, in Indonesia, democracy must not only deal with Islam with various values and doctrines in it but also must intersect with the values of Indonesian culture which eventually form dialectic in the history of political thought and practice in this country. This paper attempts to describe the dialectic of thought and history arising from the meeting of democracy, Islam and Indonesia.